Human flourishing, tourism transformation and COVID-19: a conceptual touchstone. Issue 3 (26th May 2020) - Cheer, Joseph M.
Abstract: As the planet remains in the grips of COVID-19 and amidst enforced lockdowns and restrictions, and possibly the most profound economic downturn since the Great Depression, the resounding enquiry asks—what will the new normal look like? And, in much the same way, tourism aficionados, policy makers and communities are asking a similar question—what will the tourism landscape, and indeed the world, look like after the pandemic? As casualties from the crisis continue to fall by the wayside, the rethinking about what an emergent tourism industry might resemble is on in earnest. Many are hopeful that this wake-up call event is an opportunity to reshape tourism into a model that is more sustainable, inclusive and caring of the many stakeholders that rely on it. And some indicators, though not all, point in that direction. In line with this, the concept of 'human flourishing' offers merits as an alternative touchstone for evaluating the impacts of tourism on host communities. Human flourishing has a long genesis and its contemporary manifestation, pushed by COVID-19 and applied to travel and tourism, further expands the bounds of its application. Human flourishing has the potential to offer more nuanced sets of approaches by which the impact of tourism on host communities might be measured. The challenge remaining is how to develop robust indices to calibrate human flourishing policy successes.